Local and Transregional Networks of Women in Late Medieval Mecca and the Mamluk Empire - Hafiz, Mona (AUC Knowledge Fountain, 2025)
This thesis examines the local and transregional networks of women in Mecca during the ninth/fifteenth century, as represented in the biographical dictionaries of al-Sakhāwī (d. 902/1497), Ibn Fahd (d. 885/1480), and al-Fāsī (d. 832/1429). It combines qualitative and quantitative methods in order to analyze the family, knowledge, and travels networks of women in late medieval Mecca and the Mamluk empire. It argues that Meccan women’s social and intellectual roles extended beyond their families, to other families, scholars, and regions. Simultaneously, the thesis focuses on Mecca as a central node in the networks that tied together different regions of the Mamluk empire, and it examines the city’s position within these networks from the perspective of women. It argues that ḥadīth transmission and travel demonstrate that Meccan and non-Meccan women played important social, intellectual, and economic roles that helped keep Mecca connected to the other regions of the Mamluk empire.